آليات دعم المؤسسات الناشئة في الجزائر - خضرة, زغيدي; ايمان, جميل; شيماء, بركات (جامعة الوادي - University of Eloued, 2023)
"تعتبر المؤسسات الناشئة من الركائز الأساسية في تحقيق التنمية الاقتصادية والاجتماعية وهو ما جعل الجزائر في الآونة الأخيرة تتوجه نحو تبني فكرة المؤسسات الناشئة وتعمل على تجسيدها وانجاحها. حيث تهدف هذه الدراسة الى الالمام بالجانب النظري للمؤسسات الناشئة والتعرف على اليات تمويلها،ابراز الجهود التنظيمية التي انتهجتها الجزائر لتجسيد المؤسسات الناشئة والتعرف على اسهامات هيئات المرافقة والدعم لتلك المؤسسات في الجزائر. ولقد تم التوصل الى إن الجزائر اتخذت جملة من الإجراءات لتوفير كل الدعائم القانونية، التنظيمية والمالية الى جانب توفير أجهزة الدعم والمرافقة لتلك المؤسسات الناشئة والتي بدورها حققت نتائج واسهامات معتبرة الا انها تبقى لا تعكس تطلعات الدولة. " "Start-ups are the basic pillars in achieving economic and social development, which is why Algeria has recently moved to adopt the idea of Start-ups and works to be successful, The study aims to define the theoretical side of Start-ups and to know the mechanisms of their financing, to show the organizational efforts adoped by Algeria for Starts-ups and to identify the contributions of Algerians supporting organization. We concluded that Algeria has taken a set of measures to provide all the legal, organizational and financial pillars, in addition to providing support and accompanying devices for these Starts-ups, which in turn have achieved significant results and contributions, but they do not reflect the aspirations of the state "
Keywords: المؤسسات الناشئة، هياكل الدعم، الجزائر.; Start-ups; Support Structures; Algeria.